The edges of trauma : explorations in visual art and literature - Bényei, Tamás, 1966-; Stara, Alexandra, 1967- (Cambridge Scholars Publishing, 2014)
A collection of essays by an international group of scholars, The Edges of Trauma: Explorations in Visual Art and Literature addresses the vast cultural and discursive construction that trauma has become in recent decades. Unravelling aspects of representing, narrating, testifying to trauma and of sharing or conveying traumatic non-experience, many of the essays offer new perspectives on traditionally central topics of trauma studies, including shellshock, sexual abuse, the Holocaust, AIDS an ...